Family Group Decision Making: Implementation in Child Welfare in the Province of Ontario - Tansley, Lee Loralin (My University, 2009)
The Ministry of Children and Youth Services has embarked on a Transformation Agenda that suggests a fundamental re-orientation of child welfare services in Ontario from an expert-led model to one which promotes family participation in child welfare decision making. Family Group Decision Making, also referred to as Family Group Conferencing, is an approach that encourages collaboration between child welfare workers and the family group (which includes the immediate family, relatives and friends). Alongside child protection mediation and Aboriginal approaches, Family Group Decision Making forms one of the Alternative Dispute Resolution (ADR) mechanisms advanced in the Transformation Agenda as outlined in Bill 210.
While Family Group Decision Making does facilitate conflict-resolution and will ideally significantly reduce the time spent in court over anyone case, or even in some cases, successfully divert cases from court involvement, it's fundamental purpose is as a planning tool for the family to make decisions for the safety and well-being of a child designated as at risk or in need of protection. With the advancement of the Transformation Agenda in Ontario in November 2006, it is anticipated that Family Group Decision Making will be implemented as a service in many of the fifty-three Children's Aid Societies in Ontario, and that it will be particularly useful in high-conflict, high-complex cases, although it may also be utilized in other contexts where decision making regarding a child's future is needed.
The purpose of this study is to examine how Children's Aid Societies are implementing and carrying out the practice of Family Group Decision Making/Family Group Gonferencing as one of the three approved Alternate Dispute Resoulution methods required to be considered under Bill 210, and to examine the degree to which each of the programs studied provides a service that adheres to the Family Group Conferencing Model for Ontario.
The study is based on indepth, face-to-face qualitative interviews with approved Family Group Decision Making coordinators involved with child welfare agencies in Ontario. The interviews explored Family Group Decision Making program design and implementation factors. Findings indicate that programs are closely adhering to the Ontario model, and that overall the coordinators who provide the service are extremely positive about this approach to working with families. Issues of debate include whether coordinators located "in-house" jeopordize the neutrality of the program, and if identifying Family Group Decision Making as an Alternative Dispute Resoulution mechanism to be utilized particularly in high-conflict, high-complex cases denies other families that would appreciate engaging in such a process as early on as possible in their involvement with child welfare.
Keywords: Social Work; Social Work